Atlantis, the lost empire - Hahn, Don; Murphy, Tab; Wise, Kirk (Walt Disney ; distributed in the Philippines by Viva Video, 2002)
Hidden deep below the ocean surface is one of the greatest mysteries of all time--the Lost City of Atlantis. Join the world's most highly qualified crew of experts led by "adventure capitalist" Commander Rourke (Garner) and Milo Thatch (Fox), a linguist who knows the ancient Antlantean language, as they board the incredible 1,000-foot submarine, the Ulysses, and head deep into the mysteries of the sea, hoping to reveal the secrets of Atlantis.